Rethinking Islamic Pedagogy: The Interface of Theology and Tafsīr - Shahin Rahman (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
This article explores the conception of knowledge in two distinct yet related disciplines of the Islamic sciences–namely, theology and Qurʾānic exegesis. As this article is both a historical and an educational enquiry, it adopts an interdisciplinary approach in offering a critical analysis of the pedagogies through which Muslim scholars attained and transmitted such knowledge during the first few centuries of Islam. Its findings suggest that both disciplines ought to be studied in light of one another in a way that is relevant to the learners’ own contexts. The paper concludes by offering new perspectives in developing curricula for both disciplines in line with educational pedagogic research.